Gene function rather than reproductive mode drives the evolution of RNA helicases in sexual and apomictic Boechera - Kiefer, Markus; Nauerth, Berit; Volkert, Christopher; Ibberson, David; Loreth, Anna; Schmidt, Anja (Genome biology and evolution, 2020)
Abstract. In higher plants, sexual and asexual reproductions through seeds (apomixis) have evolved as alternative strategies. Evolutionary advantages leading t
Gesehen am 25.08.2020